Anti-NMDA Autoimmune Encephalitis Post-COVID-19 Vaccination in a Pediatric Patient: A Case Report - Alabssi, Haila; Almulhim, Nouf F.; Al-Omari, Mohammed; Safar, Ayat H. (Neuropediatrics, 2023)
Post-coronavirus disease 2019 (COVID-19) vaccination encephalitis is rarely reported particularly in the pediatric population. Herein, we report the first case of postvaccination anti-N-methyl-d-aspartate (NMDA) encephalitis in close temporal association with receiving COVID-19 vaccine in a pediatric patient. The patient is a 13-year-old female who received the first dose of the Pfizer–BioNTech COVID-19 vaccine and presented with subacute neurological and psychiatric symptoms and eventually confirmed the diagnosis of anti-NMDA autoimmune encephalitis. The patient recovered after receiving intravenous immunoglobulins and steroids.
Keywords: SARS-COV-2; vaccination; autoimmune encephalitis; neurological complications; vaccine adverse effects